Acute Peritonitis: A Rare Complication Revealing Intestinal Tuberculosis - Sabbah.M,; Trad.D,; Jemmali.C,; Jouini, R; Elloumi, H; Bibani.N,; Ouakaa.A,; Gargouri.D, (Journal of Spleen And Liver Research, 2019)
Intestinal tuberculosis diagnosis is often difficult because of non-specific symptoms, miming many other conditions such as malignancy, infectious disease, and inflammatory bowel disease. Free intestinal perforation is an uncommon but life-threatening complication of intestinal tuberculosis, associated with high morbidity and mortality.
Keywords: Intestinal tuberculosis diagnosis; infectious disease; inflammatory bowel disease